Performance of Wheat as Affected by Different Irrigation Levels and Sowing Dates (The Agriculturists, 2017)
The experiment was conducted to determine the effect of irrigations and sowing dates on growth and yield performance of wheat in the experimental field of Sher-e-Bangla Agricultural University, Dhaka, Bangladesh during the period of November 18, 2012 to March 30, 2013. The experiment was comprised of two factors, viz. factor A: two irrigations namely irrigation (I) and no irrigation i.e. control (I0), and factor B: three sowing dates such as S1: 1st sowing on 18 November, S2: 2nd sowing on 03 December and S3: 3rd sowing on 18 December. The experiment was laid out in a split plot design with three replications. Irrigation was assigned in the main plot, while sowing time was in the sub-plots. Data on grain yield and different yield contributing characters were taken after harvest. Results indicated that the highest grain yield was obtained with I (2.915 t ha-1) and S1 (2.983 t ha-1). The interaction of irrigation (I) and sowing on 18 November (S1) showed the maximum yield (3.387t ha-1), spike length (17.08 cm), 1000 grain weight (43.4 g), spikelets spike-1 (20.03) and grain spike-1 (65.58) of wheat.The Agriculturists 2016; 14(2) 77-85